1999
DOI: 10.1038/sj.bjc.6690785
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer risk among women with psychiatric admission with affective or neurotic disorders: a nationwide cohort study in Denmark

Abstract: There is a considerable interest in the possible relationship between psychosocial factors and the onset of breast cancer. This cohort study was based upon two nationwide and population-based central registers: The Danish Psychiatric Central Register, which contains all cases of psychiatric admissions, and The Danish Cancer Registry, which contains all cases of cancer. The register-linkage was accomplished by using a personal identification number. The study population comprised all women admitted to psychiatr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 24 publications
1
7
0
1
Order By: Relevance
“…Little is known about the role that depression plays in the etiology of breast cancer. Of a few studies concerning this relation, three found significantly increased risk (Gallo et al 2000;Jacobs and Bovasso 2000;Peled et al 2008), one study insignificantly increased risk (Hahn and Petitti 1988) (similarly to our observation), whereas the study by Hjerl et al (1999) noted no association.…”
Section: Discussionsupporting
confidence: 84%
“…Little is known about the role that depression plays in the etiology of breast cancer. Of a few studies concerning this relation, three found significantly increased risk (Gallo et al 2000;Jacobs and Bovasso 2000;Peled et al 2008), one study insignificantly increased risk (Hahn and Petitti 1988) (similarly to our observation), whereas the study by Hjerl et al (1999) noted no association.…”
Section: Discussionsupporting
confidence: 84%
“…Finally, it needs to be considered that all three studies finding negative associations between depression and breast cancer incidence [33,39,43] and six studies finding positive associations [40-42, 44, 47, 48] included fewer than 220 individuals that developed breast cancer, while all studies finding positive associations had numbers of individuals developing breast cancer ranging from 229 to 2,892 cases of breast cancer [38,45,46,[49][50][51]. Thus, the small number of breast cancer cases could be another explanation for the negative associations between depression and breast cancer incidence.…”
Section: Discussionmentioning
confidence: 99%
“…Gallo et al [70]and Jacobs and Bovasso [71]reported an association between depression and breast cancer. A population-based cohort study of nearly 67,000 women reported no association between a psychiatric admission and breast cancer risk [72]. In addition, two recent prospective cohort studies involving over 12,000 Finnish women reported no association between measures of anxiety/depression and risk of breast cancer [73, 74].…”
Section: Resultsmentioning
confidence: 99%